Sosialisasi Strategi Usaha UMKM Mbak Atik - Isra Kesuma; Anggita Kumala Sari; Atika Frimalendra; Viona Ramifa Reja; Vivi Nila Sari (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
Micro, Small, and Medium Enterprises (MSMEs) has long been recognized as an important pillar in a country's economic development. In the 21st century, MSMEs are increasingly gaining attention from the government, academia, and the general public as the driving motor of sustainable and inclusive economic growth. MSMEs have unique characteristics that distinguish them from large companies. They generally have a smaller scale, a limited number of employees, and limited access to financial and technological resources. Nonetheless, MSMEs have great potential in creating jobs, encouraging innovation, and improving public welfare. The existence of MSMEs has a significant economic impact. They became a major source of income for many families, reduced unemployment rates, and increased per capita income. MSMEs also play a role in reducing economic and regional disparities, as they often operate in rural and remote areas that are less affordable by large companies. In addition, MSMEs also play a role in promoting economic and environmental sustainability. In its smaller businesses, MSMEs tend to use resources efficiently and contribute to sustainable economic development. Many MSMEs are involved in sectors such as renewable energy, waste treatment, and environmentally friendly products However, MSMEs still face various challenges. Some of these include limited access to financing, a shortage of managerial skills, and limitations in utilizing technology.